MCT1 is a new prognostic biomarker and its therapeutic inhibition boosts response to temozolomide in human glioblastoma - Miranda-Gonçalves, Vera (2021)
Background: Glioblastomas (GBMs) present remarkable metabolism reprograming, in which many cells display the “Warburg effect”, with the production of high levels of lactate that are extruded to the tumour microenvironment by monocarboxylate transporters (MCTs). We described previously that MCT1 is up-regulated in human GBM samples, and MCT1 inhibition decreases glioma cell viability and aggressiveness. In the present study, we aimed to unveil the role of MCT1 in GBM prognosis and to explore it as a target for GBM therapy in vivo. Methods: MCT1 activity and protein expression were inhibited by AR-C155858 and CHC compounds or stable knockdown with shRNA, respectively, to assess in vitro and in vivo the effects of MCT1 inhibition and on response of GBM to temozolomide. Survival analyses on GBM patient cohorts were performed using Cox regression and Log-rank tests. Results: High levels of MCT1 expression were revealed to be a predictor of poor prognosis in multiple cohorts of GBM patients. Functionally, in U251 GBM cells, MCT1 stable knockdown decreased glucose consumption and lactate efflux, compromising the response to the MCT1 inhibitors CHC and AR-C155858. MCT1 knockdown significantly increased the survival of orthotopic GBM intracranial mice models when compared to their control counterparts. Furthermore, MCT1 downregulation increased the sensitivity to temozolomide in vitro and in vivo, resulting in significantly longer mice survival. Conclusions: This work provides first evidence for MCT1 as a new prognostic biomarker of GBM survival and further supports MCT1 targeting, alone or in combination with classical chemotherapy, for the treatment of GBM.